China-US great-power rivalry : the competitive dynamics of order-building in the Indo-Pacific - Chan, Lai-Ha; Lee, Pak K. (New York : Routledge, 2024)
"This edited volume examines the competitive dynamics of two order-building projects in the Indo-Pacific, namely China's Belt and Road Initiative (BRI) and the US-led Free and Open Indo-Pacific (FOIP). Foci are on how far the two major powers are able to use institutional projects to (re)order the region of the Indo-Pacific to suit their policy preferences, and on how regional powers perceive and navigate between the two ordering projects. This book discusses a wide array of actors in the Indo-Pacific, covering the two major powers of China and the United States, middle powers of Australia and New Zealand, India, Japan, South Korea and Taiwan, and institutional actors of ASEAN, AUKUS, the Quad and the Pacific Islands Forum. Drawing on the concept of international order, the chapters examine the actor-specific foreign policies in relation to the rivalry between the FOIP and the BRI. This accessible book will be a go-to resource for anyone looking for how the two great powers garner legitimacy and followership for their own version of ordering project, and how regional powers respond to the dynamic competition and navigate between China and the US, and between the forces of liberal democracy and autocracy"--
Introduction: The competitive dynamics of order-building in the Indo-Pacific -- Can China create a stable illiberal regional order through the BRI?: A study of China-Myanmar economic corridor -- Competing Sino-US AUKUS narratives: The intended and unintended outcomes of 'Naming and Shaming' -- Australia and New Zealand in the Indo-Pacific: How and why the Pacific Islands look to authoritarian China? -- India and the US-China great power rivalry: Navigating between the BRI and the FOIP -- Regional order-building in the Indo-Pacific: Japan as a geopolitical alternative -- Trapped into an existential cage: Korea's hedging between China and the US -- Ideology and market linkages: Taiwan and the preservation of the US-led hegemonic order through soft power and geoeconomics -- Decentred? ASEAN's struggle to accommodate great power competition -- A 'Weak(ened)' quad in the Indo-Pacific: What do its strategic narratives tell us?
Keywords: Geopolitics -- Indo-Pacific Region; Balance of power; World politics -- 1989-; China -- Foreign relations -- United States; United States -- Foreign relations -- China; Indo-Pacific Region -- Foreign relations -- China; China -- Foreign relations -- Indo-Pacific Region; Indo-Pacific Region -- Foreign relations -- United States; United States -- Foreign relations -- Indo-Pacific Region; Indo-Pacific Region -- Strategic aspects